Celebrity Humanitarianism: The Ideology of Global Charity - Killoran-McKibbin, Sonja (UnderCurrents: Journal of Critical Environmental Studies, 2014)
Celebrity Humanitarianism: The Ideology of Global Charity. By ILAN KAPOOR. Routledge, 2013. 44.95 Reviewed by Sonja Killoran-McKibbin The back cover promised a “hyper-critical porpoise with a purpose,” and though I wasn’t entirely sure what to expect, I was not disappointed by this book. In Celebrity Humanitarianism: The Ideology of Global Charity, Ilan Kapoor cleverly and humorously attacks the celebrity charity peddlers, the “coffee-pusher philanthropists,” and the NGO superstars who dominate our conception of international aid. Using a Žižekian framework to carry out a refreshing ideology critique, Kapoor prods the assumptions implicit within celebrity humanitarianism to reveal its ideological basis and the underlying interests such actions serve. While Kapoor focuses on only a handful of notorious celebrity humanitarians, he insists that the individual celebrities in his book are merely some of the more colourful examples of a broader trend. Most importantly, Kapoor avoids the trite and banal and refuses to return to the all too easy suggestion that something is better than nothing. Instead, Kapoor’s text skilfully addresses the role of celebrity charities by systematically deconstructing the manner in which they justify and support the very inequities that they purport to challenge. By asking “Do they know that it’s Christmas?” almost thirty years ago, Band Aid set off the growing role of celebrities as an authoritative voice on global poverty. Yet the issue is under-discussed and rarely critiqued, making Kapoor’s cutting and insightful analysis long overdue. The book begins by exploring the hyper-celebrities who claim to speak for, witness, or represent poverty. Using Bono, Bob Geldof, Madonna, and Angelina Jolie as examples, Kapoor demonstrates how such celebrity charity work is used for individual profit and to mask the root causes of inequality. By offering the opportunity to do good through consumerism, such work feeds into the capitalism’s elusive promise of jouissance—or the eternal promise of enjoyment. Celebrity humanitarianism showcases the excessive lifestyles of celebrities, supporting their individual brand but also glorifying and marketing their excessive lifestyles as the ultimate promise of capitalism. Celebrities in this way are used to embody a justification of the current economic system at the same time as they claim to work to change it. Support for the decadence of the rich glorifies the inequality on which capitalism is based and obfuscates the very conditions that create poverty. Moreover, these stars act as witnesses and authorities on the poverty of the third world and situate third world subjects as victims, perpetuating the issues of inclusion and exclusion within such actions. Next to come under Kapoor’s gaze are the private foundations established and maintained by billionaires, such as the Bill and Melinda Gates Foundation and George Soros’ Open Society Institute. Calling such endeavours “decaf capitalism,” Kapoor argues that they allow people to continue with business as usual and that “it is charity that helps decaffeinate capitalism. It masks and purifies corporate ills, acting as a countermeasure to socioeconomic exploitation.” Foundations highlight the benevolence of corporate moguls and effectively hide the mechanisms through which they obtain such wealth. These acts keep people engaged and complicit with the corporate order and effectively depoliticize systems of inequality while undermining public mechanisms to improve social conditions and situating private initiatives as appropriate solutions. Finally, the book addresses those non-governmental organizations that have situated themselves as types of celebrities in their own right. From Médecins Sans Frontières (MSF) to Oxfam, such charities not only seek celebrity endorsements but have also developed their own personae and brand. Kapoor suggests that such charities, in many ways, represent an element of commodity fetishism in our late capitalist culture—distancing ourselves from elements of poverty while at the same time providing us with an outlet for our anxieties about global injustice. By constructing a “permanent emergency regime” these charities thrive on the spectacle of disaster and demand immediate action. They cultivate an anti-theoretical activism by suggesting that crisis makes immediate action essential—and unquestionably benign — leaving no time for analysis and portraying such reflection as inactive and necessarily detrimental. In this fashion such organizations encourage us to allow them to do the work for us, effectively delegating our beliefs to commodities. The absence of theorizing and the urgency of action effectively glosses over the manner in which the forms of new humanitarianism that such charities engage in are neoimperial endeavours. The complicity of NGOs in “humanitarian war” is made invisible by the parade of spectacularized emergencies. While Kapoor points to some of the ways the celebrity charity regime might be transformed, he is also quite clear that these reformist proposals are limited. They result in nothing more than a compromise with the system and do not address the depoliticizing tendencies of such international action. Drawing again on Žižek, Kapoor calls for an uncompromising politics that demands revolutionary change. While I welcome Kapoor’s call for a revolutionary overthrow of the current global order and his rejection of sanctioned resistance, I must admit that I was left feeling somewhat unsatisfied by his insistence on revolutionary inaction. What of confronting antagonisms through unsanctioned resistance? While Kapoor advocates the imagining of new political possibilities that are distinct from inaction, as they ultimately must be followed by the material work for their creation, Kapoor deals with a lot in his last few pages, and perhaps that is part of the problem. While he urges the reader to see the opportunities in the contradictions it is difficult not to wish for more than a few pages to bring together his revolutionary proposal. Nonetheless, this could also be seen as Kapoor not letting his readers off the hook for their own complicity by pushing them to consider these tendencies beyond the bound pages. Overall Kapoor has crafted an engaging and entertaining text that deftly employs an all too familiar and visible phenomenon to bring to light the ideology embedded within it. SONJA KILLORAN-MCKIBBIN is a PhD Candidate in the Faculty of Environmental Studies at York University. Her work explores the intersections of international aid and extractive industries.